A new freshwater hyphomycete species of Actinocladium in Stictographaceae (Asterinales) from Yunnan Province, China - Geng, Yun-Wu; Xu, Rong-Ju; Zhao, Qi; Zhu, Ying-An (Phytotaxa, 2026)
During an investigation into the diversity of lignicolous freshwater fungi along a north–south latitudinal gradient in the Asian region, two collections were obtained from submerged wood in freshwater habitats in Yunnan Province, China. Morphological comparison and multi-gene phylogenetic analysis of combined LSU, SSU and ITS sequence data identified the new collection as a novel species, namely Actinocladium jizhua. This species is characterized by macronematous, mononematous, cylindrical conidiophores, monoblastic conidiogenous cells, and distinctive stauriform conidia consisting of an obpyramidal basal part and usually 2–3 radiating arms. Phylogenetic analysis showed that A. jizhua formed a distinct branch within Stictographaceae and was closely related to A. aquaticum, but differs from A. aquaticum in having longer conidiophores and conidia. A comprehensive description and illustration of this new species are provided.